Vaccines and Drugs : Characteristics of Their Use to Meet Public Health Goals - Milstien, Julie B. (World Bank, Washington, DC, 2013)
The major characteristics of vaccines and drugs are reviewed and contrasted in seven key areas: research and development, the market, supply sources, regulation, procurement, financing, and access. The comparison helps to identify areas where access could be enhanced. These conclusions are drawn: (1) While public investment in R&D has been more frequent for vaccines than for drugs, it has normally covered only a fraction of R&D costs. Concerted action is needed to stimulate development of innovative public health products, with public-private partnerships being a way to stimulate work towards a specific goal. (2) Drugs and vaccines face different market conditions that affect the ability to forecast demand. While for drugs, use depends on individual willingness to pay; the vaccine market depends on government willingness to pay, based on epidemiological justification for use of a product. (3) The supply landscape differs for drugs and vaccines, with fewer vaccine manufacturers. This limits competition, compared to the case of generic drug products. Strict control of the supply chain for vaccines minimizes leakage, and makes differential pricing easier to implement. (4) A joint approach to the regulatory process for drugs and vaccines will have benefits, especially as their regulation is normally controlled by a single agency within a country. Risk-benefit assessments by the US FDA do not consider global implications, creating a need for capacity to do risk-benefit assessments in developing countries. (5) Similar procurement principles could be applied to the prequalification process for drugs and vaccines. (6) Societies often undervalue prevention in health care, which impacts vaccine prices and financing. (7) Activities that enhance access to drugs will also enhance vaccine access, although the relative importance of different factors inhibiting access may differ. Both differential pricing as well as compulsory licensing may be considered.